UYDU İMGELERİNE STEGANOGRAFİK YÖNTEMLER KULLANARAK KONUM VE YER BİLGİSİ GİZLEME - SÖNMEZ, FATMA NUR (Fırat Üniveristesi, 2022)
Dijital ortamda veri aktarılırken veri güvenliği ve gizliliği giderek daha önemli hale gelmiştir. Bunu sağlamak için birçok yöntem geliştirilmiştir. Steganografi de bu yöntemlerden biridir. Steganografi, mesajları veya verileri bir medyaya gizleme bilimidir. Steganografi de veriler karşı tarafa aktarılırken video, ses, metin, protokol ve görüntü gibi ortamlar kullanılır. Görüntü steganografisin de yaygın olarak kullanılan yöntemlerden biri an az anlamlı bit (LSB) tekniğidir. Bu çalışma da uydu üzerinden almış olduğumuz 128x128 ve 256x256 boyutlarında ki 14 farklı imgeye konum ve yer bilgisi LSB tekniği kullanılarak 6, 7 ve 8. bite gizlenmiştir. Görüntülerde ki bozulmaları önlemek ve PSNR değerini arttırmak için gizlenen verilerin tersi alınıp veri gizleme işlemi yapılmıştır. PSNR değeri hesaplanıp görüntüde ki bozulmalar gözlemlenmiştir.

Data security and privacy have become more and more important when transferring data in the digital environment. Many methods have been developed to achieve this. Steganography is one of these methods. Steganography is the science of hiding messages or data in a media. Steganography also uses media such as video, audio, text, protocol, and image, while data is transferred to the opposite party. One of the commonly used methods in image steganography is the least significant bit (LSB) technique. In this study, the location and location information of 14 different images in 128x128 and 256x256 dimensions that we received over the satellite have been hidden in 6, 7 and 8 bits by using LSB technique. In order to prevent distortions in the images and to increase the PSNR value, the data hiding has been performed by inverting the hidden data. PSNR value has been calculated and the distortions in the image have been observed.
Hiding location and location information to satellite images using steganographic methods
Keywords: Bilim ve Teknoloji; Bilgisayar Mühendisliği Bilimleri-Bilgisayar ve Kontrol